2016
DOI: 10.3390/scipharm84040685
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization Mechanism of Ionic Surfactant on Curcumin Nanocrystal against Electrolytes

Abstract: We have successfully developed curcumin nanosuspension intended for oral delivery. The main purpose is to improve bioavailability through enhancing its solubility. The nanoparticles were stabilized using various stabilizers, including polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), sodium carboxymethylcellulose (Na-CMC), d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS), and sodium dodecyl sulfate (SDS). The average diameter of particles, microscopic appearance, and sedimentation of each preparati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…BM was expected to comminute the remaining larger particles that were left behind from the HPH, thus leading to small sized PlantCrystals with homogenous particle size. The further decrease in size was expected to increase the physical stability of the PlantCrystals [ 11 ] and to further increase the amount of plant components extracted. Consequently, to prove this theory, the third part of the study was conducted by milling plant material with HPH, BM and with a combination of HPH and BM, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BM was expected to comminute the remaining larger particles that were left behind from the HPH, thus leading to small sized PlantCrystals with homogenous particle size. The further decrease in size was expected to increase the physical stability of the PlantCrystals [ 11 ] and to further increase the amount of plant components extracted. Consequently, to prove this theory, the third part of the study was conducted by milling plant material with HPH, BM and with a combination of HPH and BM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is an industrially feasible and environmentally friendly process that avoids the use of organic solvents. The equipment required is low-cost, freely available and meanwhile established in many laboratories world-wide [ 10 , 11 , 12 , 13 , 14 ]. The feasibility of the PlantCrystal technology was proven in previous studies, where PlantCrystals were shown to increase the antimicrobial and antifungal activity of various plant materials [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous solutions of PVA of 1%, 3%, and 5% were used for the preparation of PNP in both techniques. The amount of surfactant plays an essential role in the emulsication-solvent evaporation process, by the protection of the droplets containing the PLGA against coalescence 65,66. Fig.…”
mentioning
confidence: 99%
“…When neutral polymers are used, a shift in the shear plane away from the surface was observed, resulting in lower values for zeta potential. 45 The polynomial regression equation generated for the coded factors is shown below…”
Section: Effect Of Independent Variables On Zeta Potentialmentioning
confidence: 99%
“…The effect of the parameters is clearly observed in the 3D plots shown in Figure 1A-F. As per the reports, an increase in the PVA concentration increases the particle size due to the increased viscosity of the dispersion medium, resulting in decreased attrition between balls and particles and also leading to greater amount of coating on the particle surface. [43][44][45][46] The increase in the amount of ACF was found to increase the particle size. This could be possibly due to the increased amount of drug in the dispersed phase that Figure 1 Three-dimensional plots showing the effect of independent variables on particle size.…”
mentioning
confidence: 99%